Dose-dependent Clinical Spectrum and Management of Glyphosate-surfactant Herbicide Poisoning: A Case Report - Jaswanth Kumar Pasim; Vignessh Raveekumaran (Journal of Clinical and Diagnostic Research)
Glyphosate-Surfactant Herbicide (GlySH) poisoning, though less common than Organophosphate (OP) poisoning, poses significant clinical challenges due to its dose-dependent toxicity and the lack of specific antidotes. This report presents two cases with contrasting presentations. Case 1 involved a 32-year-old male with diabetes who ingested 150-200 mL of GlySH in a suicide attempt. He developed gastrointestinal symptoms, severe lactic acidosis, hypotension, and multiorgan dysfunction, requiring intensive care, intubation, and aggressive treatment. In contrast, in Case 2, a 27-year-old female with no comorbidities, ingested around 20-50 mL of GlySH and exhibited milder symptoms such as throat burning, hypoglycaemia, and tachycardia, which resolved with symptomatic treatment and intravenous fluids. For both cases, the cornerstone of treatment included fluid and electrolyte correction, along with supportive management. These cases underscore the dose-dependent nature of GlySH toxicity. Misdiagnosis is most common, as OP poisoning results in delayed treatment and exacerbation of such conditions. Treatment remains primarily supportive, following poisoning guidelines. Therefore, these cases call for better diagnostic guidelines and preventive measures to reduce the mortality associated with GlySH, especially in agricultural settings.